2000
DOI: 10.1029/2000jd900092
|View full text |Cite
|
Sign up to set email alerts
|

Effective diffusivity as a diagnostic of atmospheric transport: 2. Troposphere and lower stratosphere

Abstract: It is also demonstrated that the lower limit of the barrier at the stratospheric polar-vortex edge, i.e., the "sub-vortex" transition, varies in altitude throughout the winter. In the Antarctic the transition generally occurs at 380 K and is sometimes as low as 350 K. In the Arctic the transition is higher, rarely occun'ing below 400 K and frequently occurring above 450 K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

59
304
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 225 publications
(368 citation statements)
references
References 24 publications
59
304
1
1
Order By: Relevance
“…Indeed, using contour advection, Kowol-Santen [1998] found that the PV contours at the tropopause grow much slower than the PV contours both in the troposphere and in the stratosphere. This is in agreement with Haynes and Shuckburgh [2000], who applied a diagnostic introduced by Nakamura [1996]. They even proposed that the minimum in effective diffusivity at the tropopause level can be used for an alternative definition of the tropopause.…”
Section: Ste In the Extratropicssupporting
confidence: 85%
“…Indeed, using contour advection, Kowol-Santen [1998] found that the PV contours at the tropopause grow much slower than the PV contours both in the troposphere and in the stratosphere. This is in agreement with Haynes and Shuckburgh [2000], who applied a diagnostic introduced by Nakamura [1996]. They even proposed that the minimum in effective diffusivity at the tropopause level can be used for an alternative definition of the tropopause.…”
Section: Ste In the Extratropicssupporting
confidence: 85%
“…2). The general aspects are consistent with the effective diffusivity derived from passive tracer calculations (Haynes and Schuckburgh 2000). Kyy is substantial in the winter hemisphere at mid-latitudes, particularly outside the polar vortex in the stratosphere, and is also remarkable in the mid-latitudes troposphere with relation to the breaking of the baroclinic waves.…”
Section: Space-time Distribution Of Kyysupporting
confidence: 85%
“…Transport processes in the troposphere play a key role for the distribution of water vapor. In the vicinity of the tropopause and in particular across the subtropical jet stream, large gradients of water vapor exist due to the barrier effects of the tropopause (Haynes and Shuckburgh, 2000; Pan et al, 2004;Flentje et al, 2007;Kunz et al, 2011b). In the tropics, the low temperatures at the tropopause lead to strong freeze-drying (Jensen and Pfister, 2004;Fueglistaler et al, 2009;Schiller et al, 2009).…”
Section: Introductionmentioning
confidence: 99%